1997
DOI: 10.1074/jbc.272.20.13419
|View full text |Cite
|
Sign up to set email alerts
|

The SH3 Domain of Amphiphysin Binds the Proline-rich Domain of Dynamin at a Single Site That Defines a New SH3 Binding Consensus Sequence

Abstract: Amphiphysin is an SH3 domain-containing neuronal protein that is highly concentrated in nerve terminals where it interacts via its SH3 domain with dynamin I, a GTPase implicated in synaptic vesicle endocytosis. We show here that the SH3 domain of amphiphysin, but not a mutant SH3 domain, bound with high affinity to a single site in the long proline-rich region of human dynamin I, that this site was distinct from the binding sites for other SH3 domains, and that the mutation of two adjacent amino acids in dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
224
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(232 citation statements)
references
References 39 publications
8
224
0
Order By: Relevance
“…P4 blocks the binding of dynamin 1 to amphiphysin and prevents the recruitment of dynamin 1 to the endocytic complex. Biochemical assays showed that this peptide is highly specific and binds with high affinity to a unique site in the dynamin-proline rich domain (Grabs et al 1997;Kittler et al 2000). Treated neurons were then stimulated and used for subcellular fractionation or FM1-43 imaging as described below.…”
Section: Dynamin 1 Inhibitor Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…P4 blocks the binding of dynamin 1 to amphiphysin and prevents the recruitment of dynamin 1 to the endocytic complex. Biochemical assays showed that this peptide is highly specific and binds with high affinity to a unique site in the dynamin-proline rich domain (Grabs et al 1997;Kittler et al 2000). Treated neurons were then stimulated and used for subcellular fractionation or FM1-43 imaging as described below.…”
Section: Dynamin 1 Inhibitor Treatmentmentioning
confidence: 99%
“…To obtain more direct evidence of the role of dynamin 1 in the altered synaptic vesicle endocytosis in Aβ-treated neurons, we examined whether inhibition of dynamin 1 would cause a similar membranous build-up of amphiphysinin in cultured hippocampal neurons. To inhibit dynamin 1 activity, we used a dynamin 1 inhibitory peptide (P4) which blocks the binding of dynamin 1 to amphiphysin and prevents the recruitment of dynamin 1 to the endocytic complex (Grabs et al 1997;Kittler et al 2000). When these neurons were treated with 50 μM P4 for 30 minutes prior to stimulation they did not show any change in the amphiphysin membrane-to-cytosol ratio when compared to untreated stimulated neurons (Fig.…”
Section: Inhibition Of Dynamin 1 Caused Accumulation Of Amphiphysin Amentioning
confidence: 99%
“…Self-assembly of dynamin into oligomers activates the GTPasestimulating effect of this domain (Muhlberg et al, 1997;Sever et al, 1999). Through its Proline Rich Domain (PRD), dynamin is further able to interact with a number of SH3 domain containing proteins involved in endocytosis, such as amphiphysin, cortactin, endophilin, Grb2, intersectin and Src (Gout et al, 1993;Miki et al, 1994;Seedorf et al, 1994;Grabs et al, 1997;Ringstad et al, 1997;Foster-Barber and Bishop, 1998;Yamabhai et al, 1998;McNiven et al, 2000). There is increasing evidence that dynamin is involved in the late stages of clathrin-coated vesicle formation, most likely in pinching off of clathrin-coated pits (Kosaka and Ikeda, 1983;Carter et al, 1993;van der Bliek et al, 1993;Damke et al, 1994;Damke et al, 1995;Sever et al, 2000;Damke et al, 2001;Narayanan et al, 2005).…”
Section: Dynaminmentioning
confidence: 99%
“…A yeast lysate containing HA-Inp52 was prepared as previously described (41), except that the lysis buffer contained 3 mg/ml bovine serum albumin and 1% Nonidet P-40. In addition, beads with immobilized His 6 -tagged polypeptides were preincubated in buffer containing 1 mg/ml bovine serum albumin in Tris-buffered saline, pH 7.5, for 1 h at 4°C.…”
Section: Immobilization Of and Binding To Bacterially Expressed Hismentioning
confidence: 99%